Foreign Fighters, Human Rights and Self-Determination in Syria and Iraq: Decoding the Humanitarian Impact of Foreign Fighters in Practice - Conduit, D.; Rich, Ben (2016)
Foreign fighters have become inextricably linked to perceptions of human rights abuses in the Syria and Iraq wars, particularly since the Islamic State group founded its caliphate. This paper explores the human rights impact of foreign fighters in the conflicts, noting that while foreign fighters have been involved in grave human rights abuses, such behavior has not been uniform and must be differentiated by group and role. In this regard, it is argued that while foreign fighters have overwhelmingly had a negative impact on most human rights indicators, fighters in some groups have positively impacted the Right to Self-Determination. Further, the paper notes that while foreign fighters have been large-scale perpetrators of human rights abuses, one must also consider the propaganda value of such acts because foreign fighter-led violence is more newsworthy globally than local-led violence.